Study about Wound Healing, Evolution of Cancer and War on Cancer - Ming C. Liau; Linda Liau Baker (Recent Developments in Medicine and Medical Research Vol. 8, 2021)
This review highlights the impact of wound onto the evolution and therapy of cancer. The objective of this review is to explore the mechanism of wound healing and its relationship to the evolution and therapy of cancer. Wound healing requires the proliferation and the terminal differentiation (TD) of progenitor stem cells (PSCs), which are the precursors of cancer stem cells (CSCs).Healing wound is not a big deal. If the functionality of chemo-surveillance is intact such as healthy people who can maintain a steady level of wound healing metabolites functioning as differentiation inducers (DIs) and differentiation helper inducers (DHIs).Wounds are always successfully healed without having to put up any effort, just to let the nature to do the healing. Medications such as suture and antibiotics are subsidiary to speed up the healing or to prevent infection. Acute wound affects the functionality of chemo-surveillance only temporarily, which is quickly recovered to return to the normal state. It is the chronic wound such as persistent infectious diseases or exposure to toxic chemicals including carcinogens for a long time that produces damaging effect on the functionality of chemo-surveillance.Chronic wound prompts the production of inflammatory cytokines to cause excessive urinary excretion of wound healing metabolites to affect wound healing. Without sufficient wound healing metabolites to terminate the proliferation of PCSs, it is very easy for PSCs to evolve into CSCs. It takes only a single hit to silence TET-1 enzyme to complete the transition, which is well within the reach of PSCs equipped with abnormally active methylation enzymes (MEs).CSCs can then progress to faster growing cancer cells by the activation of oncogenes or the inactivation of (AML). Cancer due to wound not healing properly is not unique to MDS and AML. It is rather a common phenomenon. War on cancer can be easily won if the battle is conducted following the nature’s course to heal the wound, just like the success of wound healing without having to put up any effort in healthy people. Therefore, the best strategy to win the war on cancer is to restore the functionality of chemo-surveillance by the employment of DIs and DHIs and to prevent the loss of wound healing metabolites through anti-cachexia chemicals such as phenylacetylglutamine. Then the nature will take its course to stop the proliferation of cells with abnormal MEs that include CSCs, PSCs, and all cancer cells. Destruction strategy to kill cancer cells is definitely counter indication. It creates more damages to the functionality of chemo-surveillance to stop the growth of cells with abnormal MEs. Inability of destruction strategy to put away CSCs is a deciding factor to deny the success of destruction strategy to win the war on cancer.